2009
DOI: 10.1057/thr.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

The Right Answers to the Wrong Questions? Observations on Skill Development and Training in the United Kingdom's Hospitality Sector

Abstract: This article is informed by a literature review of current research on skills and skills development undertaken for People 1st, the Sector Skills Council covering hospitality, gaming, leisure and tourism activities in England. The article suggests that much government policy towards skills needs in the sector is based on a number of erroneous assumptions. Fundamentally, State training interventions chiefl y involve education and training supply, and not low levels of employer demand for training, or low employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…During the commodification process, family labor is invested to commercial accommodation, and domestic skills become inputs into service production. It has been observed that in commercial homes, family members are emotionally 7 and physically incorporated into commercial hospitality activities at different levels (Baines & Gelder, 2003;Lynch, 2003Lynch, , 2005, ranging from accommodating the occasional paying guests during peak season, to attracting and hosting customers throughout the year (Lashley, 2009).…”
Section: Commodification Of the Rural Homementioning
confidence: 99%
“…During the commodification process, family labor is invested to commercial accommodation, and domestic skills become inputs into service production. It has been observed that in commercial homes, family members are emotionally 7 and physically incorporated into commercial hospitality activities at different levels (Baines & Gelder, 2003;Lynch, 2003Lynch, , 2005, ranging from accommodating the occasional paying guests during peak season, to attracting and hosting customers throughout the year (Lashley, 2009).…”
Section: Commodification Of the Rural Homementioning
confidence: 99%
“…The value and challenges of work placements, internships or work integrated learning has therefore long been debated in the field of hospitality management education. Closely connected to this has been the debate about how students of hospitality develop "soft" and "hard" skills (Lashley, 2009;Lashley & Barron, 2006;Sisson & Adams, 2013;Weber, Finley, Crawford & Rivera, 2009). Hospitality students also benefit from exposure to "problem-based learning" approaches to assessment, as this most closely mirrors the multi-disciplinary challenges they will face in industry (Kivela & Kivela, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The results outlined above suggest that informal training approaches, such as buddy systems, were often used in hospitality organizations as noted in the literature review (e.g., Eaglen et al, 1999;Lashley, 2009). This is especially true for small hospitality organizations, where no support system and limited budgets for training and developing employees is available, unlike chain organizations that have resources and support departments, such as HR departments.…”
Section: Discussionmentioning
confidence: 80%
“…Training in the Hospitality Industry A review of the literature on training in the hospitality industry (see for example, Eaglen, Lashley, & Thomas, 1999;Baum, 2002;Lashley & Thomas, 402 A. E. E. Sobaih 2005; Monk & Ryding, 2007;Lashley, 2009;People 1st, 2010) has shown that there is, indeed, a shortage of training provided for hospitality staff and that many firms operate without formal training approaches. The literature stresses that informality and relatively unsophisticated practices are major traits of hospitality organizations, and this is particularly true for small and medium enterprises (SMEs) (Jameson, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%